The Relationship Between Pregnant Women’s Knowledge, Attitudes, and Behaviors Toward Tetanus Toxoid Immunization - Sofyan Andri; Noviardi noviardi; Nizan Dani Oktama (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Tetanus Toxoid (TT) immunization remains a critical strategy in preventing maternal and neonatal deaths caused by tetanus. Despite its proven effectiveness, TT immunization coverage in Indonesia including in Pekanbaru City remains below target. Among the contributing factors are pregnant women's levels of knowledge, attitudes, and behaviors, which are believed to significantly influence immunization uptake. Objective: This study aimed to assess the relationship between pregnant women’s knowledge, attitudes, and behaviors and their participation in TT immunization programs across three health center areas in Pekanbaru: Simpang Tiga, Rejosari, and Okura. Methods: A descriptive analytic quantitative study with a cross-sectional design was conducted, involving 111 pregnant women who attended antenatal care (ANC) visits in May 2025. Data were analyzed using the Chi-Square test, Spearman Rank correlation, Cramer’s V, and logistic regression, with a significance level set at p < 0.05. Results: The study found statistically significant differences in knowledge, attitudes, and behaviors among the three health center areas (p < 0.05). Notably, good knowledge did not always correspond to positive attitudes—many well-informed respondents still exhibited negative attitudes. However, a strong correlation was observed between attitude and behavior (Cramer’s V = 0.552). Logistic regression revealed that knowledge (OR = 0.201; p = 0.005), attitude (OR = 2.068; p = 0.036), and behavior (OR = 5.660; p < 0.001) significantly influenced TT immunization uptake, with behavior emerging as the most dominant factor. Conclusion: Efforts to improve TT immunization coverage must go beyond knowledge-based education and focus on fostering positive attitudes and reinforcing supportive behaviors. Behavior-centered interventions and effective communication by health workers are essential to strengthen immunization outcomes.